Fiber morphology in fast growth Gmelina arborea plantations - Moya Roque, Róger; Tomazelo Fo, Mario; Canessa Amador, Edwin (Instituto de Ecología, A.C., 2016)
Gmelina arborea is planted in large areas of forest with the objective of producing solid wood using well known silvicultural techniques and taking advantage of the properties of the wood quality of fast-growing tree species managed in short rotation systems. The aim of this study was to analyze the morphology and dimension of fibers from the pith to the bark in trees from fast growth plantations in northern Costa Rica.The results indicate that fiber morphology is irregular in both diameter and shape; with 1 to 4 septa, abundant crystals deposited in fiber lumina and minutely bordered pits with oblique and nonvestured apertures. Fiber length, width and cell wall thickness increased with tree age in the early stages. Lumen diameter was not correlated with tree age.